Exploring vegetation's role in enhancing ant-based coffee berry borer control in an agroforestry system - NANANG TRI HARYADI; AGUNG SIH KURNIANTO; NILASARI DEWI; GELANG ARUM KEMANGI SUKMA; ERVATAMIA SYAH DEVARIGATA; YESSICA MELIA RANI SUYITNO; NUR LAILA MAGVIRA; ANGGUN SAUSAN FIRDAUS (Society for Indonesian Biodiversity, 2024)
Abstract. Haryadi NT, Kurnianto AS, Dewi N, Sukma GAK, Devarigata ES, Suyitno YMR, Magvira NL, Firdaus AS. 2024. Exploring vegetation's role in enhancing ant-based coffee berry borer control in an agroforestry system. Biodiversitas 25: 491-501. The coffee industry faces a serious threat from coffee berry borer pests, causing significant economic losses. This research aims to explore the potential of using ants as a biological control method in coffee plantations, as well as the influence of shade on ant communities. The research was conducted in the Sumberjambe and Silo Sub-districts using purposive sampling methods to collect ant specimens with the beating sheet method. Specimens were identified in the laboratory, and data were analyzed using the Shannon-Wiener diversity index, the Evenness index, and the Margalef species richness index. The results showed 17 ant genera in Sumberjambe and 13 in Silo, with 7 of them acting as predators. The analysis indicated low diversity (H’=0.88-1.56) with the dominance of the Dolichoderus and Lasius genera at both locations. A high evenness index in Sumberjambe (E=0.75) indicated a uniform distribution, whereas a moderate value in Silo indicated a less uniform ant distribution (E=0.45). Species richness at both locations was considered low (Dmg=0.66-0.91). Comparative tests between the two locations did not show a significant difference in the diversity of ants that could potentially act as predators. This study also includes an analysis of tree species vegetation at the agroforestry sites, with Albizia chinensis trees showing the highest importance value in Silo (INP=209.37). This indicates the significant role of this plant in the ant agroforestry community. The Tapinoma genus (Pearson corr.=0.996, p-value=0.0467) and Solenopsis genus (Pearson corr.=0.993, p-value=0.0432) showed a very strong positive correlation with Albizia plants. However, some other combinations showed weaker correlations or approached zero, indicating that the number of vegetation species did not greatly influence their presence or abundance. This research provides insight into the diversity of ants, their potential role as predators of the coffee berry borer, and the relationship between ants and vegetation on two coffee-based agroforestry fields in Jember District, Indonesia.